Potential and challenges of blockchain technology implementation in Higher Education: A systematic literature review - Gusi Putu Lestara Permana; Komang Ayu Widyani Martatika (Review of Management, Accounting, and Business Studies, 2024)
This study examined the potential applications and challenges of implementing blockchain technology within higher education systems. Blockchain, known for its decentralized and immutable nature, attracted significant interest due to its ability to provide secure, transparent, and efficient data management. In the context of higher education, blockchain has the potential to revolutionize academic record management, enhance verification processes, prevent fraud, and ensure the authenticity of credentials. This systematic literature review identified key use cases, such as academic credentialing, student data management, and the protection of intellectual property in research. Despite its promising potential, the adoption of blockchain in higher education, particularly in Indonesia, remained in its early stages. The study discussed major obstacles to implementation, including technical limitations, high costs, limited awareness, and regulatory barriers. Addressing these challenges required further research and collaboration between academic institutions, government agencies, and technology providers to enable widespread adoption. The review emphasized the need for a comprehensive framework to guide the practical implementation of blockchain, ensuring its benefits could be fully realized in educational environments.